2010
DOI: 10.1038/ng.603
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for vitiligo identifies susceptibility loci at 6q27 and the MHC

Abstract: We conducted a genome-wide association study of generalized vitiligo in the Chinese Han population by genotyping 1,117 cases and 1,429 controls. The 34 most promising SNPs were carried forward for replication in samples from individuals of the Chinese Han (5,910 cases and 9,916 controls) and Chinese Uygur (713 cases and 824 controls) populations. We identified two independent association signals within the major histocompatibility complex (MHC) region (rs11966200, Pcombined=1.48x10(-48), OR=1.90; rs9468925, Pc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
5
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(157 citation statements)
references
References 46 publications
6
143
5
3
Order By: Relevance
“…It is also possible to encounter a series of autoimmune diseases, such as bullous epidermolysis, vitiligo and/or psoriasis. Some authors consider that vitiligo pathogenesis associated with IBD is autoimmune or, in other cases, genetic [10,11]. The incidence of vitiligo in the general population is 0.3%, with a significantly lower rate compared to its 1.1% incidence among UC patients [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to encounter a series of autoimmune diseases, such as bullous epidermolysis, vitiligo and/or psoriasis. Some authors consider that vitiligo pathogenesis associated with IBD is autoimmune or, in other cases, genetic [10,11]. The incidence of vitiligo in the general population is 0.3%, with a significantly lower rate compared to its 1.1% incidence among UC patients [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Further evidence for the generalized involvement of the CCR6 gene region in autoimmune disease risk comes from two independent GWAS on vitiligo each of which identified strongly associated SNPs located 30 --175 kb upstream from CCR6. 10,11 The CYP2R1 and DHCR7 loci reached genome-wide significance in two GWAS on vitamin D insufficiency. 12,13 CYP2R1 rs10741657 and DHCR7 rs12785878 were found to be associated with T1D, a condition associated with vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…When this gene is overexpressed, it makes cells more vulnerable to oxidative stress (Thompson et al, 2009), an important mechanism for melanocyte destruction. The two genes are FGFR10P, which encodes a fibroblast growth factor receptor and can play a role in cell cycle progression in some disorders (Acquaviva et al, 2009), and the chemokine receptor 6 gene (CCR6) (Quan et al, 2010). Another HLA-oriented study by de Castro et al (2010) examined the gene encoding the discoidin domain receptor 1 (DDR1).…”
Section: Studies Involving the Human Leukocyte Antigenmentioning
confidence: 99%
“…Overall, these candidate associations with NSV support the assertion that NSV susceptibility loci are shared with loci associated with other autoimmune diseases (Ying et al, 2010). In another genome-wide association study, susceptibility loci were found on chromosome 6 and in the MHC (Quan et al, 2010). Genotyping of 6,623 vitiligo patients and 10,740 controls was carried out, and analyzed for 34 SNPs which deemed promising from a www.intechopen.com…”
Section: Studies Involving the Human Leukocyte Antigenmentioning
confidence: 99%